Student Performance in Field Experience Program and Educational Institution Satisfaction - Novita, Mona; Solihin, Muhammad; Istikomah, Istikomah; Kurniawan, Sugeng; Umatin, Ana Rosyidatu (JURNAL AL-TANZIM, 2022)
The purpose of the study was to describe the level of satisfaction of partner schools with the performance of PPLK II IAI Yasni Bungo students. The study used a quantitative approach with a descriptive survey method. The form of the survey implementation in this study used a questionnaire. Questionnaires were given to the population, namely partner schools that were appointed and selected by the IAI Yasni Bungo campus in the implementation of the PPLK II program, which was chosen by random sampling, namely six schools that were accredited B and represented regional regions for Bungo and Tebo regencies and represented each level of education program. Data collection techniques using questionnaires, interviews, observation, and documentation. Data analysis was carried out through stages; 1) descriptive statistical analysis, 2) testing requirements analysis, and 3) hypothesis testing. The research findings show that the satisfaction of partner schools with the performance of IAI Yasni Bungo students in implementing the PPLK II program is in the "Satisfactory" category.